Random and AB diblock copolymers of tricyclodecanemethanol urethane methacrylate with styrene: synthesis and morphology characterization - Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2008)
A monomer design having a bulky terminal tricyclodecane (TCD) unit linked via hydrogen bondable urethane to an ethyleneoxy methacrylate unit, and capable of generating three-dimensional honeycomb patterns upon solvent casting has been investigated. Random copolymers as well as a diblock copolymer Poly(Sty42-b-TCD18) of this monomer with styrene were prepared by free-radical polymerization route and atom transfer radical polymerization (ATRP) route. Morphology characterization was carried out using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. Particle size was measured by dynamic light scattering measurements (DLS). Irrespective of the wide differences in molecular weight and polydispersity index values, the random copolymers having TCD content >30 mol % were found to form microporous films upon solvent casting from a THF/water 9:1 solvent combination. The amount of TCD in the copolymer was found to have an influence on the pore size formed. The diblock copolymer formed microspheres ∼200 nm in diameter. The thermal properties of all the polymers were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), and the copolymers were found to have good thermal stability. © 2008 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 46: 1278–1288, 2008

Random copolyesters containing perylene bisimide: flexible films and fluorescent fibers - Nisha, S. Kumari; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Random copolyesters of poly(L-lactic acid) (PLLA) and [poly-(1,4-cyclohexylenedimethylene-1,4- cyclohexanedicarboxylate)] (PCCD) incorporating varying mol ratios of perylene bisimide (PBI) were developed via a high-temperature solution-blending approach. PCCD incorporating PBI was developed by melt polycondenzation followed by a polyester-polyester transesterification reaction between PCCD PBI and PLLA. The polymers exhibited good solubility in common organic solvents and formed free-standing films, which showed bright red emission upon irradiation with ultraviolet radiation. A solid state fluorescence quantum yield of 10% was observed for this PBI based polyester, which was much higher than that reported in literature for PBI based polymers in the solid state (<1%). Strong red fluorescent nanofibers of these polymers were successfully constructed by electrospinning technique. A random copolyester incorporating donor based on oligo(p-pheneylenevinylene) (OPV) and PBI as acceptor chromophore was also synthesized and fluorescence microscopy images of the electrospun fibers of this polymer exhibited blue, green and red emission upon excitation at different wavelengths. The high temperature solution blending approach involving a high molecular weight polymer and a suitably functionalized it conjugated molecule described here is a unique method by which 1D nanostructures of a wide range of pi-conjugated chromophores could be fabricated having strong fluorescence, with the scope of application in nanoscale optoelectronics, biological devices, as well as sensing.
Keywords: flexible film; fluorescent nanofibers; luminescent film; oligo(p-phenylenevinylene); perylene bisimide

Rylene diimide-based alternate and random copolymers for flexible supercapacitor electrode materials with exceptional stability and high power density - Sharma, S.; Soni, R.; Kurungot, S.; Asha, S. K. (Journal of Physical Chemistry C, 2019)
Donor–acceptor pi-conjugated polymers are emerging as interesting electrode materials for supercapacitor device applications. They offer an exciting possibility of charge storage in both positive and negative electrodes because they are both p- and n-dopable. The ambipolar charging enables higher operating voltage, which can afford higher specific energy and power densities. The donor–acceptor design can be either donor-alternate-acceptor or donor-random-acceptor. This architectural variation has the potential to modify the charge storage; yet surprisingly not much literature data is available exploiting this aspect. This paper explores the alternate and random geometries of donor–acceptor π-conjugated polymers based on naphthalene diimide or perylene diimide (PDI) as the acceptor component and benzodithiophene (BDT) as the donor component and their application as composite electrode materials in a type III supercapacitor device. Results show that the donor–acceptor alternate design involving P(PDI-alt-BDT) is an excellent supercapacitor electrode material with specific capacitance of 113 F g–1 with excellent stability up to 4000 cycles and almost 100% retention of the initial capacitance in a single-electrode setup in a PC-LiClO4 organic electrolyte. A flexible supercapacitor device was also fabricated which shows areal capacitance of 35 mF cm–2 at a current density of 0.5 mA cm–2, which is promising for commercial applications.

Room temperature photocurable PEEK polymer formulations for high-performance 3D printing applications - Pal, Shibam; Gaikwad, Yogesh; Asha, S. K. (ACS Applied Engineering Materials, 2024)
Digital light processing (DLP) technology was employed to 3D print acrylate-modified poly(ether ether ketone) (PEEK). PEEK and modified PEEK (mPEEK incorporating pendant pentadecyl chain) polymers were synthesized and end-capped with urethane acrylate units. These end-modified PEEK polymers were combined with commercially available (meth)acrylic cross-linkers and photoinitiator to create photocurable resin formulations suitable for DLP 3D printing. The resulting 3D-printed parts exhibited remarkable mechanical strength, with a Young’s modulus of 2.1 GPa. This surpassed the mechanical properties of commercial acrylate resin 3D-printed parts and achieved approximately 55% of the Young’s modulus of reported commercial PEEK polymer. Notably, the thermal properties of the 3D-printed materials were impressive, including a high glass transition temperature of 140 °C and stability with only around 10% weight degradation occurring at approximately 400 °C. These innovative resins demonstrated excellent printability with high resolution, enabling the fabrication of intricate shapes, including complex dental materials by DLP 3D printing. Their versatility extends to potential applications in dentistry, automobile manufacturing, and robotics.

Recyclable l-glutamic acid-based polyester schiff base cross-linker for 3D printing applications - Kamble, Ganesh N.; Ghute, Aaditi P.; Asha, S. K. (ACS Applied Polymer Materials, 2026)
An l-amino acid-based polyester Schiff base cross-linker was developed from amine-functionalized polyester and biobased methacrylate vanillin. Vanillin, one of the few biobased and aromatic compounds readily available on an industrial scale, has recently garnered significant attention from the polymer community. The l-amino acid-based polyester Schiff base cross-linker (P3) was synthesized by condensing the aldehyde group of methacrylate vanillin with the amine group of the l-glutamic acid polyester. This polymeric cross-linker was used in resin formulations consisting of isobornyl acrylate as a reactive diluent and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as the photoinitiator for digital light processing (DLP) three-dimensional (3D) printing. The resulting 3D-printed parts exhibited good mechanical properties, with a Young's modulus of 1.5 GPa, and high thermal stability, with a T max of 410 degrees C. The chemical degradability of the 3D-printed materials was demonstrated in a mixture of tetrahydrofuran and diethylene triamine (1:1) at 80 degrees C for 48 h. The reusability of the recovered resin was demonstrated by adding fresh methacrylate vanillin and photoinitiator, followed by 3D printing using a DLP 3D printer. The 3D-printed parts produced from the recycled resin retained substantial mechanical properties, with a Young's modulus of 1.39 GPa, and thermal stability, with a T max of 390 degrees C.
Keywords: 3D printing; chemical degradation; covalent adaptable network; l-glutamicacid; Vanillin